Satire and Socio-Political Critique in Wole Soyinka's Opera Wonyosi: A Study of Corruption and Military Mal-Administration in Post-Colonial Nigeria - Alice Blessing Ogundiya; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2024)
This research examines Wole Soyinka's play Opera Wonyosi through the lens of postcolonial theory, focusing on themes of corruption and military mal-administration in post-independence Nigeria. Adopting a qualitative research methodology, this study employs content analysis to evaluate the play’s narrative structure, character development, and satirical elements. Ania Loomba's postcolonial theory serves as the theoretical framework, providing a nuanced understanding of the socio-political critique embedded in the text. By analyzing the enduring impact of colonial power structures and the dynamics of authority in postcolonial societies, the research uncovers the ways in which Soyinka critiques the pervasive corruption and moral decay perpetuated by military regimes. The study also explores the complexities of identity and resistance as depicted through the play’s characters, particularly highlighting how postcolonial identities are shaped by both indigenous and colonial influences. Through Soyinka’s sharp satire, the research underscores the grotesque alliance between political leaders and organized crime, illustrating the systemic dysfunction and social decay that ensue. The findings reveal that Opera Wonyosi not only mirrors the socio-political realities of Nigeria but also resonates with broader postcolonial struggles against oppression and injustice. Ultimately, this study contributes to the understanding of Soyinka’s work as a powerful cultural critique and a call for social reform, reinforcing its significance within the canon of postcolonial literature.